PENGUJIAN TEMBUS DIELEKTRIK MINYAK JARAK SEBAGAI ALTERNATIF PENGGANTI ISOLASI PADA MINYAK TRAFO - Purwiyanto Purwiyanto; Galih Mustiko Aji (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2017)
To detach two or more conductors which have voltage in electrical power system, it is needed an insulation, then among conductors which have voltage do not occur electricity sputtering. Oil is an insulation material which muchused to insulate and refrigerate the high voltage electrical tools. Oil insulator is an liquid insulation which derived from petroleum or crude oil which specifically processed until having characteristics as an insulator, but nowdays theworld development demands for safe and eco-friendly products to decrease the effects of global warming. This condition opens the opportunity to use renewable energy which derived from vegeTabel oil. The breakdown voltagetest of curcas liquid oil insulation materials at various electrode using transformator gulf oil as comparator, it aims to study insulation power of curcas oil towards the breakdown voltage with various temperature and gap spacing. Basedon the result of the test, it shows that the breakdown voltage of curcas oil dielectric has the highest point, then it is possible to be developed being transformator insulation oil.